Surface Plasmon Enhancement of an InGaN Quantum Well Using Nanoparticles Made of Different Metals and Their Combinations - Saleem, Muhammad Farooq; Peng, Yi; Li, Liuyan; Zhou, Bangdi; Yang, Jia; Lu, Haixia; Li, Guoxin; Huang, Lixiang; Chen, Jie; Wei, Wenwang; Yang, Yanlian; Wang, Yukun; et al. (Nanomaterials (Basel, Switzerland), 2022)
Surface plasmon (SP) enhancement of photoluminescence (PL) from a green-emitting InGaN/GaN quantum well (QW) using nanoparticles (NPs) made of different metals and their combinations was investigated. The NPs were formed by annealing the metal films in N2 followed by rapid cooling. Four-fold enhancement in PL intensity was achieved using random metal NPs made of Cu on Mg (Cu-Mg) double metal film that was more than two folds of the enhancement observed by AgNPs. Reversing the order of metal film deposition (Mg on Cu) resulted in much lower PL intensity due to significantly different NPs size distribution as the given annealing conditions did not cause homogeneous alloying of the two metals. The results pave the way for the application of NPs of relatively low-cost unconventional metals and their combinations in the SP enhancement of LEDs.